Climate change impacts on heat stress in Brazil—Past, present, and future implications for occupational heat exposure - Bitencourt, Daniel Pires; Alves, Lincoln; Shibuya, Elisa Kayo; da Cunha, Irlon; de Souza, João Paulo (International journal of climatology, 2021)
Climate change has caused an increased occurrence of heat waves. As a result of rising temperatures, implications for health and the environment have been more frequently reported. Outdoor labour activities deserve special attention, as is the case with agricultural and construction workers exposed to extreme weather conditions, including intense heat. This paper presents an overview of heat stress conditions in Brazil from 1961 to 2010. It also presents computer‐simulated projections of heat stress conditions up to the late 21st century. The proposed climate analysis drew on historical weather data obtained from national weather stations and on reanalysis data, in addition to future projections with the ETA (regarding the model's unique vertical coordinate) regional forecast model. The projections took into consideration two Representative Concentration Pathways (RCP)—the 4.5 and 8.5 climate scenarios, namely, moderate and high emissions scenarios, respectively. Heat stress was inferred based on the wet‐bulb globe temperature (WBGT) index. The results of this climate analysis show that Brazilian outdoor workers have been exposed to an increasing level of heat stress. These results suggest that future changes in the regional climate may increase the probability of heat stress situations in the next decades, with expectations of WBGT values greater than those observed in the baseline period (1961–1990). In terms of spatial distribution, the Brazilian western and northern regions experienced more critical heat stress conditions with higher WBGT values. As a response to the increased frequency trends of hot periods in tropical areas, urgent measures should be taken to review public policies in Brazil. Such policies should include actions towards better working conditions, technological development to improve outdoor labour activities, and employment legislation reviews to mitigate heat impacts on occupational health. The most critical area subject to heat stress is the west of Brazil, mainly within the Midwestern region. Particularly, it is in the Midwestern region that most workers perform outdoor activities under a heavy workload. It was observed that the frequency of days per year with high WBGT has increased considerably in the current climate period. Besides, an increased occurrence of high WBGT was projected for the next decades.